Avaliação do potencial anti-inflamatório do extrato hidroalcoólico da casca da Luehea divaricata - LINS, Jadiel de Abreu Pimenta (2019)
Luehea divaricata popularly known as horse whip is used in folk medicine, however studies evaluating the pharmacological activity of this plant species are scarce. Therefore, the aim of this study was to evaluate the anti-inflammatory action of the hydroalcoholic bark extract of Luehea divaricata (EHLd). The anti-oxidant effect of EHLd was evaluated by the DPPH method and Raw 264.7 cell cytotoxicity was evaluated by the MTT (methyltiazole tetrazolium) method as well as its anti-inflammatory effect which was evaluated by NO and gene expression of IL-1β and IL-6 by Griess and real-time PCR (RT-qPCR) methods, respectively. In addition, the anti-inflammatory effect of EHLd has also been evaluated in mice with acute lung injury (APD). Forty-eight Swiss mice (05 groups) received oral pretreatment with either EHLd (50 mg / kg, 100mg / kg and 250mg / kg) or saline (1mL / kg) and were induced one hour after APD by intranasal LPS instillation (30,000UE / 10μg / 50μL / animal). After 24h, bronchoalveolar lavage (BAL), whole blood (TS) and organs were collected for analysis. Total and differential leukocyte count from both lavage and blood, IL-1β and IL-6 gene expression by lung RT-qPCR were analyzed and histological analysis of the lungs, kidneys and liver was performed. Through high performance liquid chromatography (HPLC), the EHLd showed as major peaks the substances Rhoifolin, Isorhoifolin, Naringin, Kaempferol - 3 - caffeoyl glucoside 7 - 0 Glucoside, and Nuzhenide. EHLd, at a concentration of 250μg / mL, showed anti-oxidant effect by capturing 55% of free radicals. EHLd showed low cytotoxicity at all concentrations tested from 50μg / mL to 250 μg / mL (p <0.05). It was also observed that EHLd has anti-inflammatory effect, since it reduced NO levels and IL-1β and IL-6 gene expression showed anti-inflammatory activity at all tested concentrations. Compared to the in vivo study, pretreatment with EHLd reduced cell migration, mainly from neutrophils, to the lungs of DPA mice, and also reduced the expression of lung IL-1β and IL-6 genes, as well as, reduced edema and leukocyte infiltrate in the lungs caused by LPS. In this context, Luehea divaricata extract may help in the treatment of inflammation.